The challenges of alternative labour dispute resolution. The Spanish experience - de Fuentes García-Romero de Tejada, Carlos (2025)
Spain has a consolidated system of alternative labour dispute resolution, made up of measures established by the legislator and others agreed by the most representative employers and trade union organizations. Both are analyzed and it is considered whether state action makes sense, once the agreed solution has reached a very significant stage of development. It also identifies the main challenges of autonomous conflict resolution and reviews the state of its main innovations more than four years after the entry into force of the 6th Agreement on the Autonomous Settlement of Labour Disputes.